Influence of Seed Polymer Coating and Foliar Spray with Micronutrients on Yield and Lint Quality of Bt-Cotton Hybrid (Gossypium hirsutum L.) - ANUP ARALAKKANAVAR,; SR DODDAGOUDAR,; SN VASUDEVAN,; N M SHAKUNTALA,; J M NIDAGUNDI, (Seed Research, 2026)
A field experiment was conducted during kharif 2014 at College of Agriculture, UAS, Raichur with an objective to study the influence of seed polymer coating and foliar spray with micronutrients on yield and lint quality of Bt cotton hybrid. The experiment consisted of seventeen different seed polymer coating and foliar spray treatments with micronutrients in three replications laid out in Randomized Block Design. The experimental results revealed that, seed polymer coating with ZnSO4 + FeSO4 + MgSO4 + MnSO each @ 4 g kg of seed along with two foliar sprays (0.5% +0.5% +1% +0.5%, respectively, in EDTA form except MgSO,) at an interval of ten days during flowering stage (65 AND 75 DAS) recorded significantly higher plant height (156.2 cm), chlorophyll content (45.20 SPAD values) at 90 DAS, number of bolls (41.57), boll weight (5.54 g), seed index (13.57 g) and seed cotton yield (29.03 q) compared to all other treatments and control (129.5 cm 38.90 SPAD values, 36.83, 4.35 g, 11.37 g and 24.77 q, respectively). The lint quality parameters did not show any significant difference due to seed polymer coatingand foliar spray with micronutrients in Bt cotton hybrid.